Siyasah Tanfidziyah Review of The Feasibility And Safety Of Public Transportation Of Banda Aceh - Nurhaliza, Intan; Alidar, Emk; Umur, Azmil (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2025)
The Banda Aceh City Departement has an important role in regulating and supervising various strategies public transportation of office public. Based on Law Number 22 of 2009 concerning Road Traffic and Transportation, Article 53 states that periodic testing is required for public passenger cars, buses, goods cars, trailers and attached trains operated on the road. However, in reality there are still land public transports that do not meet roadworthy standard requirements and do not carry out routine testing and continue to operate on the roads as public transport. The research method used is qualitative research with an empirical juridical approach, namely field research by examining the applicable legal provisions in accordance with the realities of society regarding the implementation of the feasibility and safety of public transport in the City of Banda Aceh. The data sources used are based on the results of interviews and observations with a number of respondents and informants who are directly related to the problem under study. The results of the research show that monitoring the feasibility and safety of public transport has not been carried out optimally due to the lack of road raid supervision. As well as low awareness of the public and public transport business actors to carry out periodic testing. According to siyasah tanfidziyah, in carrying out regular feasibility and safety tests of public transportation vehicles, which are carried out by the Banda Aceh City Transportation Service. In order to maintain order, security, prevent accidents that cause loss of life, it is appropriate and appropriate to do this to create benefits for the community.